Thermodynamic, structural, surface and transport properties of Au-Ni liquid alloy at 1150 K - Yadav, S K; Chaudhary, N; Adhikari, D (BIBECHANA, 2021)
Thermodynamic, structural, surface, and transport properties of Au-Ni liquid alloy at 1150 K were computed using different theoretical approaches. The thermodynamic properties, such as excess Gibbs free energy of mixing, enthalpy of mixing, activity and excess entropy of mixing, and structural properties, such as concentration fluctuation in long-wavelength limit and Warren-Cowley short-range order parameter were computed in the framework of Flory’s model. The effect of positive and negative values of the interchange energy parameter on the excess Gibbs free energy of mixing and concentration fluctuation in the long-wavelength limit was also observed. The surface tension and surface concentration of the system were calculated using Butler’s model. In the transport property, the viscosity of the system was calculated using Kaptay and Budai-Benko-Kaptay (BBK) models. BIBECHANA 18 (1) (2021) 184-192